Seed Dispersal Potential of Two Domestic Herbivores: Who Poops the Most Seeds? - Yadav, Harsh; Phartyal, Shyam S. (Indian Forester, 2023)
Endozoochory is an important mechanism in free-grazing ecosystems with a high potential to modify the dynamics of vegetation. Here, we examine two domestic herbivores (cow and buffalo) for their seed dispersal potential in free-grazing agroecological landscapes. Twenty fresh dung samples of each herbivore were collected, and the fresh weight of each sample was measured. The presence of viable seeds in the pile was estimated through the seedling emergence method traditionally used for soil seed bank studies. A total of 2058 seedlings of 68 species emerged from 40 dung samples; cow and buffalo dispersed 59 and 48 species, respectively, sharing 39 common species. Among them, 21 were monocots and the remaining (47) dicots. Despite the low weight of the pile of dung, there were more seeds (1298) dispersed by cow than by buffalo (760). This study concludes that domestic herbivores have a high seed dispersal potential that needs to be explored in more detail. Currently, seed dispersal is an understudied field of ecological research in India, despite the high faunal and floral diversity. Thus, this study highlights the need for more active seed dispersal research in Indian ecological studies.